Level of Water Pollution Based on Organic Material Parameters and Number of Bacteria Escherechia coli in Dumai River Estuary, Dumai City - Lubis, Nur Aisyah; Nedi, Syahril; Effendi, Irwan (Journal of Coastal and Ocean Sciences, 2021)
This research was conducted in March 2020 at the Dumai River Estuary, Dumai City, Riau Province. The purpose of this study was to analyze the parameters of OT, BOD and TOM in the Dumai River Estuary; analyzing E. coli bacteria in the Dumai River Estuary and Determining the Level of Water Pollution Based on the Content of Organic Material Parameters and E. coli in the Dumai River Estuary. The data analysis method refers to OT (SNI 06.6989.14-2004), BOD (SNI 06-2503-2009), BOT (SNI 06-6989.22-2004) and E. coli (SNI 2897-2008). The results of measuring the parameters of organic matter content in the Dumai River Estuary, OT levels ranged from 4.1 - 4.6 mg /L, BOD5 levels ranged from 21.5 - 30.6 mg /L, the TOM content in The Dumai River Estuary ranges from 104 -165 mg /L and E. coli bacteria in the Dumai River Estuary ranges from 180 - 764 MPN /100 mL. The level of pollution at the Dumai River Estuary is based on the parameters of organic matter and E. coli content, including the criteria for light pollution.